Pengaruh Suhu dan Waktu Pengeringan Terhadap Mutu Kimia dan Organoleptik Tepung Biji Durian - Ananda, Lilian; If'all, If'all; Spetriani, Spetriani; Sabariyah, Sitti; Indriasari, Yuanita; Wahid, Siti Fathurahmi (JASATHP: Jurnal Sains dan Teknologi Hasil Pertanian, 2025)
Durian seeds are a fruit by-product with potential as a food source due to their carbohydrate, protein, and fiber content. This study aimed to evaluate the effects of drying temperature and duration on yield, chemical properties, antioxidant activity, and organoleptic characteristics of durian seed flour. A completely randomized design (CRD) with two factors—drying temperature (40°C, 60°C, and 80°C) and drying time (14, 16, and 18 hours)—was used, with three replications per treatment. Results showed that both temperature and time significantly affected all observed parameters. The optimal treatment was drying at 40°C for 14 hours, yielding 55.56%, with moisture content of 1.23%, protein 3.20%, starch 28.64%, and the highest antioxidant activity (IC₅₀ = 17.12 ppm). Meanwhile, drying at 80°C for 16 hours received the highest panelist preference in terms of color, aroma, and texture. These findings suggest that durian seed flour has potential as a functional food ingredient and a natural antioxidant source. Optimizing drying conditions adds value to durian seed waste and supports its application in the food industry.